IL-10 Genetic Polymorphisms Were Associated with Valvular Calcification in Han, Uygur and Kazak Populations in Xinjiang, China - An, Yong (PLoS One, 2015)
OBJECTIVE: Valvular calcification occurs via ongoing endothelial injury associated with inflammation. IL-10 is an anti-inflammatory cytokine and 75% of the variation in IL-10 production is genetically determined. However, the relationship between genetic polymorphisms of IL-10 and valvular calcification has not been studied. The objective of this study was to investigate the association between valvular calcification and IL-10 genetic polymorphisms in the Han, Uygur and Kazak populations in China. PATIENTS AND METHODS: All of the participants were selected from subjects participating in the Cardiovascular Risk Survey (CRS) study. The single nucleotide polymorphisms (SNPs) rs1800871 and rs1800872 of the IL-10 gene were genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Three independent case-control studies involving the Han population, the Uygur population and the Kazak population were used in the analysis. RESULTS: For the Han and Kazak populations, rs1800871 was found to be associated with valvular calcification in the recessive model, and the difference remained statistically significant following multivariate adjustment (p<0.001, p=0.031, respectively). For the Han, Uygur and Kazak populations, rs1800872 was found to be associated with valvular calcification in the dominant model, and the difference remained statistically significant following multivariate adjustment (p<0.001, p=0.009, and p=0.023,respectively) CONCLUSION: Both rs1800871 and rs1800872 of the IL-10 gene are associated with valvular calcification in the Han and Kazak populations in China. Rs1800872 is also associated with valvular calcification in the Uygur population.